Opportunistic Routing Protocols In Human Working Day Model Delay Tolerant Networks (International Journal of Engineering and Computer Science, 2017)
Delay-tolerant Networks are used to enable communication in sparse mobile ad-hoc networks and other weak as well as challenged environments where traditional networking fails and new routing and application protocols are required. Experiences with DTN routing and application protocols has shown that their performance is extremely dependent on the mobility and node characteristics. Opportunistic routing protocol drives to improve wireless performance by making a good use of communication opportunities arising by chance. DTN protocols evaluation across many scenarios requires suitable simulation tools. This project presents the opportunistic networking routing simulator specifically designed for evaluating DTN routing and application protocols. Also provides users to create scenarios based on different synthetic movement as well as real-world traces. It offers a framework for implementing routing and application protocols with six well-known routing protocols